Diagnosis of Fungal Keratitis in Low-Income Countries: Evaluation of Smear Microscopy, Culture, and In Vivo Confocal Microscopy in Nepal - Hoffman, Jeremy J.; Yadav, Reena; Sanyam, Sandip Das; Chaudhary, Pankaj; Roshan, Abhishek; Singh, Sanjay Kumar; Arunga, Simon; Hu, Victor H.; Macleod, David; Leck, Astrid; Burton, Matthew J. (Journal of Fungi, 2022)
Clinically diagnosing fungal keratitis (FK) is challenging; diagnosis can be assisted by investigations including in vivo confocal microscopy (IVCM), smear microscopy, and culture. The aim of this study was to estimate the sensitivity in detecting fungal keratitis (FK) using IVCM, smear microscopy, and culture in a setting with a high prevalence of FK. In this cross-sectional study nested within a prospective cohort study, consecutive microbial keratitis (MK) patients attending a tertiary-referral eye hospital in south-eastern Nepal between June 2019 and November 2020 were recruited. IVCM and corneal scrapes for smear microscopy and culture were performed using a standardised protocol. Smear microscopy was performed using potassium hydroxide (KOH), Gram stain, and calcoﬂuor white. The primary outcomes were sensitivities with 95% conﬁdence intervals [95% CI] for IVCM, smear microscopy and culture, and for each different microscopy stain independently, to detect FK compared to a composite referent. We enrolled 642 patients with MK; 468/642 (72.9%) were ﬁlamentous FK, 32/642 (5.0%) were bacterial keratitis and 64/642 (10.0%) were mixed bacterial-ﬁlamentous FK, with one yeast infection (0.16%). No organism was identiﬁed in 77/642 (12.0%). Smear microscopy had the highest sensitivity (90.7% [87.9–93.1%]), followed by IVCM (89.8% [86.9–92.3%]) and culture (75.7% [71.8–79.3%]). Of the three smear microscopy stains, KOH had the highest sensitivity (85.3% [81.9–88.4%]), followed by Gram stain (83.2% [79.7–86.4%]) and calcoﬂuor white (79.1% [75.4–82.5%]). Smear microscopy and IVCM were the most sensitive tools for identifying FK in our cohort. In low-resource settings we recommend clinicians perform corneal scrapes for microscopy using KOH and Gram staining. Culture remains an important tool to diagnose bacterial infection, identify causative fungi and enable antimicrobial susceptibility testing.
Keywords: Microbial keratitis; Fungal keratitis; In vivo confocal microscopy; Diagnosis; Microbiology; Nepal; Cornea; Culture; Microscopy